Influence of argon on temperature modulation and neurological outcome in hypothermia treated rats following cardiac arrest. (August 2017) - Brücken, Anne; Bleilevens, Christian; Föhr, Philipp; Nolte, Kay; Rossaint, Rolf; Marx, Gernot; Fries, Michael; Derwall, Matthias
Abstract: Aim of the study: Combining xenon and mild therapeutic hypothermia (MTH) after cardiac arrest (CA) confers a degree of protection that is greater than either of the two interventions alone. However, xenon is very costly which might preclude a widespread use. We investigated whether the inexpensive gas argon would enhance hypothermia induced neurologic recovery in a similar manner. Methods: Following nine minutes of CA and three minutes of cardiopulmonary resuscitation 21 male Sprague-Dawley rats were randomized to receive MTH (33 °C for 6 h), MTH plus argon (70% for 1 h), or no treatment. A first day condition score assessed behaviour, motor activity and overall condition. A neurological deficit score (NDS) was calculated daily for seven days following the experiment before the animals were killed and the brains harvested for histopathological analysis. Results: All animals survived. Animals that received MTH alone showed best overall neurologic function. Strikingly, this effect was abolished in the argon-augmented MTH group, where animals showed worse neurologic outcome being significant in the first day condition score and on day one to three and five in the NDS in comparison to MTH treated rats. Results were reflected by the neurohistopathological analysis. Conclusion: Our study demonstrates that argon augmented MTH does not improve functional recovery after CA in rats, but may even worsen neurologic function in this model.